Influence of Ovophospholipids on Lymphocyte Subsets and Humoral Immune Response in Mice - Magdalena Lis; Marianna Szczypka; Agnieszka Suszko-Pawłowska; Aleksandra Pawlak; Łukasz Bobak; Bożena Obmińska-Mrukowicz (Molecules)
Designed hen eggs enriched in DHA and EPA are an alternative source of essential phospholipids. This study assessed the effects of ovophospholipids on lymphocyte subsets in non-immunized mice and on the humoral immune response in sheep red blood cells (SRBC)-immunized mice. Ovophospholipids were administered orally for 14 days (once a day) at doses of 100, 10, and 1 mg/kg. Ovophospholipids increased the total lymphocyte count of in the lymphoid organs. At 10 and 1 mg/kg, ovophospholipids increased the subsets of CD4−CD8− and CD4+CD8+ thymocytes but decreased the percentage of CD4+ and CD8+ thymocytes. A stimulating effect on splenocytes was particularly evident 24 h after administration of the 10 and 1 mg/kg doses. Ovophospholipids also elevated the absolute counts of CD3+ and CD19+ splenocytes. An increase in the absolute count of CD3+, CD4+, CD8+, and CD19+ lymphocytes of the mesenteric lymph nodes was observed 24 h after administration of the lowest dose. The increase in the percentage and absolute count of CD19+ cells and in the absolute count of CD3+ cells was still observed after 72 h. At all doses, ovophospholipids elevated the number of plaque-forming cells on day 4 and increased 2-mercaptoethanol-resistant antibody titer on day 7 after priming. In conclusion, ovophospholipids can modulate the immune response in mice.